Midterm Review of the Caribbean Regional Technical Assistance Centre (CARTAC). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The mid-term review was undertaken to help funding and implementing agencies foster a greater level of understanding of the Caribbean Regional Technical Assistance Center's (CARTAC) work. It ascertains activities to date and should help the Steering Committee determine optimal strategies for the Center's continuation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet